Immunologic Complications and Graft Survival in Crohn's Disease and NOD2 Mutant Non-Crohn's Disease Adult Recipients Following Intestine Transplantation. Issue 6 (June 2020) - Belyayev, Leonid; Hawksworth, Jason; Khan, Khalid; Kaufman, Stuart; Subramanian, Sukanya; Kroemer, Alexander; Loh, Katrina; Girlanda, Raffaele; Fishbein, Thomas M.; Matsumoto, Cal S.
Abstract : Background: Despite improved outcomes in the modern era of targeted immunotherapy, intestinal failure and chronic parenteral nutrition remains a significant burden for patients with Crohn's disease (CD) worldwide. Transplantation is a key component of management when a patient with CD suffers from life-threatening complications of parenteral nutrition. Nucleotide-binding oligomerization domain 2 (NOD2) mutation is a risk factor for both development of CD and intestinal allograft rejection. Methods: A retrospective review of a prospectively maintained database of intestinal transplants at a single center from 2003 to 2015 was conducted. Eleven adult patients with CD were identified and were compared with 103 adult control recipients. A sub-analysis was performed comparing the 11 CD recipients to the 13 NOD2 mutant non-CD recipients. Results: Patient and allograft characteristics were similar between the CD and control recipients. Although overall rejection-free survival was not significantly different, patients with CD suffered from more frequent, earlier, and more severe rejection compared with control patients. The onset, severity, and frequency of rejection was comparable between patients with CD and NOD2 mutant non-CD patients. There was a trend toward lower 5-year allograft survival for CD compared with control recipients (33% versus 63.3%; P = 0.19) and NOD2 mutant non-CD recipients (33% versus 57.14%; P = 0.41). Conclusions: Patients with CD remain a challenging population in intestine transplantation, and NOD2 mutant non-CD patients appear to have a similar immunologic phenotype. These high-risk recipients may require specialized immunosuppression protocols and management at experienced transplant centers.